Energy Futurology: The Renewable Energy Revolution and the Future of Global Energy Supply - Jafari, Mina; Nazarizadeh, Farhad (Management Strategies and Engineering Sciences, 2024)
The world is on the brink of a significant transformation in the energy sector. Rising concerns about climate change and the depletion of fossil fuel resources have accelerated the transition towards renewable energy sources. This study focuses on examining the global upward trend in adopting renewable technologies such as solar, wind, and hydropower. Findings indicate significant progress in the production and increased share of renewable energy in the global energy mix, attributed in part to domestic and international regulations and commitments to sustainable energy provision, as well as a growing trend in demand. Several critical factors influence this transition, including government support policies, investments, and technological innovations, which play a substantial role in creating economic opportunities, generating employment, and impacting the environment and local communities. However, despite these significant advances, challenges such as financial, technological, regulatory, and policy limitations persist, requiring targeted planning and special attention.